THE RELATIONSHIP BETWEEN SELF- ESTEEM AND STUDENTS ANXIETY IN SPEAKING: HUBUNGAN HARGA DIRI DENGAN KECEMASAN SISWA DALAM BERBICARA - Ziliwu, Elisabet (UPMI Proceeding Series, 2024)
This study was conducted to see the ability of students to speak with their deskmates in relation to a person's level of self-confidence. This study uses a quantitative research type with correlation analysis. The population in this study was 207 students with a sample of 27 students so that the sampling method used was simple random sampling. Data analysis used in this study used instrument tests (validity and reliability), assumption tests (normality and homogeneity), hypothesis tests and statistical tests (descriptive and inferential). Based on the results of the study, it can be concluded that there is a significant relationship between self-esteem and students' speaking anxiety. With a correlation value of r 0.538 with a significance of 0.000 <0.01. Ha is accepted Ho is rejected, which means there is a relationship between self-esteem and students' speaking anxiety. The higher the self-esteem, the lower the students' speaking anxiety and vice versa.